Leo Tolstoy’s sphere of concepts in the devel-opment of women’s education - Rezeda Mukhametshina, Anton Afanasev,; Kadisha Nurgali, Dinara Tolbayeva, (Opción, 2019)
The article studies the effect of Leo Tolstoy’s personality and his concept sphere on the prominent Kazakh educator Ybyrai Altyn-sarin via bibliographical, receptive, comparative, and historical meth-ods. Revealing Tolstoy’s influence on the selfless activities of Ybyrai Altynsarin is the main result of this work, e.g., establishment of schools for boys, and then the establishment of schools for girls. In conclusion, Altynsarin’s chrestomathy followed the student throughout the entire learning process, serving as a textbook and a reference book